The death of classical cinema : Hitchcock, Lang, Minnelli - McElhaney, Joe, 1957- (State University of New York Press, 2006)
"The Death of Classical Cinema uncovers the extremely rich yet insufficiently explored dialogue between classical and modernist cinema, examining the work of three classical filmmakers - Alfred Hitchcock, Fritz Lang, and Vincente Minnelli - and the films they made during the decline of the traditional Hollywood studio system. Faced with the significant challenges posed by alternative art cinema and modernist filmmaking practices in the early 1960s, these directors responded with films that were self-conscious attempts at keeping pace with the developments in film modernism. These films - Lang's The Thousand Eyes of Dr. Mabuse, Hitchcock's Marnie, and Minnelli's Two Weeks in Another Town - were widely regarded as failures at the time and bolstered critics' claims concerning the irrelevance of their directors in relation to contemporary filmmaking. However, author Joe McElhaney sheds new light on these films by situating them in relation to such acclaimed modernist works of the period as Godard's Contempt, Fellini's La dolce vita, Antonioni's Red Desert, and Resnai's Last Year of Marienbad. He finds that these modernist films, rather than being diametrically opposed in form to the work of Hitchcock, Lang, and Minnelli, are in fact profoundly linked to them."--Jacket.
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation.; Lang, Fritz, -- 1890-1976 -- Criticism and interpretation.; Minnelli, Vincente -- Criticism and interpretation.; Hitchcock, Alfred, -- 1899-1980; Lang, Fritz, -- 1890-1976; Minnelli, Vincente; Motion picture industry -- United States -- History.; Cinéma -- Industrie -- États-Unis -- Histoire.; PERFORMING ARTS -- Film & Video -- Direction & Production.; Criticism, interpretation, etc.